Application of Fish Waste Organic Fertilizer Increased Yield of Sweetcorn - Ikhsan Hasibuan; Farida Aryani; Meylinda Puspitasari (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
Bengkulu province produces 250.000 tonnes of fish every year. However, the previous research showed that almost half of the total fish caught was considered a waste. Utilizing the fish waste was needed to avoid bad smells and other environmental pollution. The research intended to transform the fish waste into organic fertilizer and evaluated its effect on sweet corn production. The main problem in transforming fish waste into organic fertilizer is that the fish waste is easy to spoil which is an unwanted physical characteristic for qualified organic fertilizer. Reducing the water content of fish waste is believed as a major factor to be avoided the spoil condition during bokashi fermentation. This research aimed to evaluate the water content levels and dosages of fish waste organic fertilizer on the growth and yield of sweetcorn. The design used in this study was a Completely Randomized Design in 3 replications. Two water content levels (J1: 75% and J2: 30%) compared to cow manure (J3), the traditional organic fertilizer. The next factor was four dosage levels of organic fertilizer that were 5, 10, 15, and 20 t/ha for D1, D2, D3, and D4, respectively. The data were then analyzed statistically with Anova and LSD 5%. The main findings of this research were as follows; Firstly, the utilization of fish waste organic fertilizer had improved sweetcorn yield productivity by 4.20 t/ha higher than that of cow manure. Secondly, the higher the water content level the better the effect on the growth and yield of sweetcorn. Lastly, the lowest dosage (5 t/ha) of fish waste organic fertilizer had an insignificant effect on the higher dosages on some sweetcorn growth and yield parameters.